Blended learning to improve students’ independence in learning basic Korean - Kamilah, Alya Darajat; Haristiani, Nuria; Triarisanti, Risa (Universitas Pendidikan Indonesia (UPI), 2021)
Although previous research has demonstrated the significance of blended learning in foreign language learning, little attention is devoted to examining the influence of blended learning on students’ basic Korean learning process. This research aims to investigate the students’ perceptions of blended learning model in learning basic Korean. A quantitative and qualitative research method was employed by collecting data from questionnaires and interviews. This research involved 20 students in a Donasi Sambil Belajar (DOSILA) program. The DOSILA program was included as a learning program that used a blended learning model with a composition of 30% of e-learning and 70% of face-to-face learning. In addition, students’ perceptions of the blended learning model were examined. The results revealed that the application of blended learning as a new learning model could improve students’ learning independence properly. The students also informed that blended learning model assisted them to learn basic Korean easily with satisfaction. However, they encountered some obstacles such as forgotten schedules and poor internet connection. The results of this research can be a reference for future research to formulate more rigorous teaching framework.